Does wearing a mask promote consumer uniqueness seeking? - Liang, Yiyuan; Peng, Qiushui; Yang, Yuqing; Wang, Jiayu; Liu, Tao (Frontiers in Psychology, 2024)
As a motivational factor, uniqueness drives individuals to seek and choose unique goods or experiences. The act of wearing masks obscures individuals’ facial features and influences their desire for uniqueness. This study aims to explore how wearing masks promotes individual uniqueness- seeking behavior. Three experiments were performed using various product categories (Starbucks coffee cups, sweatshirts, suitcases, and baseball caps) and sample types (college student and adult samples). Experiment results show that wearing masks obscures individuals’ facial features and weakens their self- perceived uniqueness, thereby increasing their willingness to actively purchase unique products. This study is the first to examine the effect of wearing masks on individuals’ choice of unique products. Practically, the results suggest that customized products can compensate for the lack of self-perceived uniqueness brought about by facial occlusion, thus providing valuable guidance for companies and retailers that offer customized services in formulating and designing marketing strategies.